2013
DOI: 10.1021/ma4008303
|View full text |Cite
|
Sign up to set email alerts
|

Coassembly of Block Copolymer and Randomly Methylated β-Cyclodextrin: From Swollen Micelles to Mesoporous Alumina with Tunable Pore Size

Abstract: Controlling interactions at the supramolecular level is of importance for the preparation by template directed synthesis of mesoporous materials with tailored pore structures. Herein we investigate the effect of randomly methylated β-cyclodextrin on the association behavior of the amphiphilic triblock copolymer Pluronic P123 in aqueous solution. Surface tension, dynamic light scattering, and viscosity measurements provide quantitative evidence that, when the cyclodextrin is added in controlled amounts to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 70 publications
1
36
0
Order By: Relevance
“…Upon increasing the concentration of RAMEB to 80 and 100 mg/mL, the R H increased to 15.5 and 31 nm, respectively, indicating the swelling of the micelles by the cyclodextrin. This was interpreted by Bleta et al as due to the hydrophobic affinity between the OCH 3 groups of RAMEB and the PPO block of the copolymer, leading to the assembly of the cyclodextrins in the interfacial layer, as shown in Figure (a). The location of the cyclodextrins in the interfacial layer also contributes to the change in the micellar curvature from spherical to ellipsoidal shape.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Upon increasing the concentration of RAMEB to 80 and 100 mg/mL, the R H increased to 15.5 and 31 nm, respectively, indicating the swelling of the micelles by the cyclodextrin. This was interpreted by Bleta et al as due to the hydrophobic affinity between the OCH 3 groups of RAMEB and the PPO block of the copolymer, leading to the assembly of the cyclodextrins in the interfacial layer, as shown in Figure (a). The location of the cyclodextrins in the interfacial layer also contributes to the change in the micellar curvature from spherical to ellipsoidal shape.…”
Section: Introductionmentioning
confidence: 89%
“…A similar template method was used by Bleta et al for synthesizing mesoporous alumina with controlled pore size, by taking advantage of the micellar co‐assembly of a triblock copolymer and methylated cyclodextrin. Valero et al concluded that methylated β‐cyclodextrins do not form pseudorotaxanes with PEO–PPO–PEO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29][30][31] The interaction between native CDs and Pluronics leading to the formation of PRs and PPRs has been described in the literature. 32,33 The substitution of the hydroxyl groups on the rims of the CD strongly modifies the aggregation behavior of the Pluronic micelles, depending on the specific nature of the substituents, [34][35][36] and the kinetics and mechanisms of the formation of the PPRs have been studied. [37][38][39] Specifically, the PRs formed with 2-hydroxypropyl β-CD and Pluronic have shown promise in the biomedical field for the treatment of Niemann-Pick disease.…”
Section: Introductionmentioning
confidence: 99%
“…And that is precisely the focus of the current research. [4] While until now, although many studies have been involved in the regulation of the particle and channel sizes, such as by changing the structure template agent, [2,5,7] adjusting the solvents [8] and nanocasting from carbon aerogels [9] etc., the report clearly accessed to continuously adjustable particle and pore sizes is still very little. Here we put forward a simple method to synthesis of alumina aerogels with free adjustable particle and pore sizes.…”
mentioning
confidence: 99%